The expression of genes coding for distinct types of glycine-rich proteins varies according to the biology of three metastriate ticks, Rhipicephalus (Boophilus) microplus, Rhipicephalus sanguineus and Amblyomma cajennense - Maruyama, S.R.; Anatriello, E.; Anderson, J.M.; Ribeiro, J.M.; Bradao, L.G.; Valenzuela, J.G.; Ferreira, B.R.; García, G.R.; Szabo, M.J.P.; Patel, S.; Bishop, Richard P.; Miranda Santos, I.K.F. de (Springer, 2010)
Ticks secrete a cement cone composed of many salivary proteins, some of which are rich in the amino acid glycine in order to attach to their hosts' skin. Glycine-rich proteins (GRPs) are a large family of heterogeneous proteins that have different functions and features; noteworthy are their adhesive and tensile characteristics. These properties may be essential for successful attachment of the metastriate ticks to the host and the prolonged feeding necessary for engorgement. In this work, we analyzed Expressed Sequence Tags (ESTs) similar to GRPs from cDNA libraries constructed from salivary glands of adult female ticks representing three hard, metastriate species in order to verify if their expression correlated with biological differences such as the numbers of hosts ticks feed on during their parasitic life cycle, whether one (monoxenous parasite) or two or more (heteroxenous parasite), and the anatomy of their mouthparts, whether short (Brevirostrata) or long (Longirostrata). These ticks were the monoxenous Brevirostrata tick, Rhipicephalus (Boophilus) microplus, a heteroxenous Brevirostrata tick, Rhipicephalus sanguineus, and a heteroxenous Longirostrata tick, Amblyomma cajennense. To further investigate this relationship, we conducted phylogenetic analyses using sequences of GRPs from these ticks as well as from other species of Brevirostrata and Longirostrata ticks.